Congenital double-double lip: A rare case report - Swati Phore; Rahul Singh Panchal (Wolters Kluwer Medknow Publications, 2017)
A double lip is a rare anomaly characterized by a horizontal fold of redundant mucosal tissue that is situated proximal to the vermilion border. It may be either congenital or acquired and has no gender or race predilection. It occurs most often in the upper lip, although both upper and lower lips are occasionally involved. Surgical intervention (simple excision) produces good functional and cosmetic results. In this report, a case of a nonsyndromic congenital maxillary double upper lip and lower lip, both are described. Double lip is of special interest in dental profession as a dental surgeon is normally the first one to diagnose this rare and uncommon condition. Authors hereby discuss a very rare condition in which both upper and lower lips are involved.